Efecto sociojurídicos de la pena de Prisión en las contravenciones de la Policía, en el cantón Machala, en el periodo del año 2012. - Lavanda Hidalgo, Milton René (2013)
With this legal trabajao I intend to present the situation of inventors against those who are punished with imprisonment from 1 to 30 days of imprisonment and financial penalty, and that after being tried and setenciados, should pay the penalty at the Centers Interim Detecion .